A combination of matrix stiffness and degradability dictate microvascular network assembly and remodeling in cell-laden poly(ethylene glycol) hydrogels. (April 2023) - Friend, Nicole E.; McCoy, Atticus J.; Stegemann, Jan P.; Putnam, Andrew J.
Abstract: The formation of functional capillary blood vessels that can sustain the metabolic demands of transplanted parenchymal cells remains one of the biggest challenges to the clinical realization of engineered tissues for regenerative medicine. As such, there remains a need to better understand the fundamental influences of the microenvironment on vascularization. Poly(ethylene glycol) (PEG) hydrogels have been widely adopted to interrogate the influence of matrix physicochemical properties on cellular phenotypes and morphogenetic programs, including the formation of microvascular networks, in part due to the ease with which their properties can be controlled. In this study, we co-encapsulated endothelial cells and fibroblasts in PEG-norbornene (PEGNB) hydrogels in which stiffness and degradability were tuned to assess their independent and synergistic effects on vessel network formation and cell-mediated matrix remodeling longitudinally. Specifically, we achieved a range of stiffnesses and differing rates of degradation by varying the crosslinking ratio of norbornenes to thiols and incorporating either one (sVPMS) or two (dVPMS) cleavage sites within the matrix metalloproteinase- (MMP-) sensitive crosslinker, respectively. In less degradable sVPMS gels, decreasing the crosslinking ratio (thereby decreasing the initial stiffness) supported enhanced vascularization. When degradability was increased in dVPMS gels, all crosslinking ratios supported robust vascularization regardless of initial mechanical properties. The vascularization in both conditions was coincident with the deposition of extracellular matrix proteins and cell-mediated stiffening, which was greater in dVPMS conditions after a week of culture. Collectively, these results indicate that enhanced cell-mediated remodeling of a PEG hydrogel, achieved either by reduced crosslinking or increased degradability, leads to more rapid vessel formation and higher degrees of cell-mediated stiffening.